Komunikasi Media FILM Studi Fenomenologi Pada Sineas-Kritikus Film dan Penikmat Film Tentang Makna Fungsi Film Wonderful Life - . Anisti (Universitas Bina Sarana Informatika, 2017)
Abstract. This study aims to build experience filmmakers about the determination of the film's theme. Of the number of movie theme, movie theme of social movements still arguably rare. Not many filmmakers who dare to take this theme for a variety of things including the film difficult to sell in the market. The difficulty competing with more popular movie themes such as film genre horror, comedy and action. However, in the year 2016 one of the filmmakers will release themed movies is a social movement Wonderful Life. The film is overall a story about children with special needs. During these special needs children considered one eye when they have the same rights and opportunities. They just need more support from their environment. This is the reason why the reality of the movie theme important to investigate. Reality does not stand alone but is emik, meaning that individual as an informant can build on the experience of meaning. Each individual will perform interpretations of reality are accepted. In this case, the individual in question is the cinematographer. The study focused on how the filmmakers to build awareness for the courage specify a movie theme. The method used phenomenological qualitative approach. The study says that the experience of every filmmaker diverse backgrounds choose a theme related to social movements but maknya movie remains the same which is difficult to market a movie-themed social movements. Keywords: movie theme, movie media, movie function